Do obesity and sleep problems cluster in the workplace? A multivariate, multilevel study - Oksanen, Tuula; Kawachi, Ichiro; Subramanian, S. V.; Kim, Daniel; Shirai, Kokoro; Kouvonen, Anne; Pentti, Jaana; Salo, Paula; Virtanen, Marianna; Vahtera, Jussi; Kivimäki, Mika (Scandinavian Journal of Work, Environment & Health, 2013)
' ' OBJECTIVES ': 'The aim of this study was to examine the co-occurrence of obesity and sleep problems among employees and workplaces. ' ' METHODS ': 'We obtained data from 39 873 men and women working in 3040 workplaces in 2000–2002 (the Finnish Public Sector Study). Individual- and workplace-level characteristics were considered as correlates of obesity and sleep problems, which were modelled simultaneously using a multivariate, multilevel approach. ' ' RESULTS ': 'Of the participants, 11% were obese and 23% reported sleep problems. We found a correlation between obesity and sleep problems at both the individual [correlation coefficient 0.048, covariance 0.047, standard error (SE) 0.005) and workplace (correlation coefficient 0.619, covariance 0.068, SE 0.011) level. The latter, but not the former, correlation remained after adjustment for individual- and workplace-level confounders, such as age, sex, socioeconomic status, shift work, alcohol consumption, job strain, and proportion of temporary employees and manual workers at the workplace. ' ' CONCLUSIONS ': 'Obese employees and those with sleep problems tend to cluster in the same workplaces, suggesting that, in addition to targeting individuals at risk, interventions to reduce obesity and sleep problems might benefit from identifying “risky” workplaces.
Keywords: clustering; Finland; health risk; multilevel; multilevel study; multivariate study; obesity; public sector; sleep; sleep problem; workplace